What are the genomic drivers of the rapid evolution of PRDM9? - Ponting, C (2011)
Mammalian Prdm9 has been proposed to be a key determinant of the positioning of chromosome double-strand breaks during meiosis, a contributor to speciation processes, and the most rapidly evolving gene in human, and other animal, genomes. Prdm9 genes often exhibit substantial variation in their numbers of encoded zinc fingers (ZFs), not only between closely related species but also among individuals of a species. The near-identity of these ZF sequences appears to render them very unstable in copy number. The rare sequence differences, however, cluster within ZF sites that determine the DNA-binding specificity of PRDM9, and these substitutions are frequently positively selected. Here, possible drivers of the rapid evolution of Prdm9 are discussed, including selection for efficient pairing of homologous chromosomes or for recombination of deleterious linked alleles, and selection against depletion of recombination hotspots or against disease-associated genome rearrangement.